The Relation of Working Discipline and Employee Performance - Dehotman, Khornelis (ADPEBI Publisher, 2023)
This paper seeks to determine the effect of work discipline on employee performance in the office staff of the Air Tiris Sub-district Head, Kampar Regency. Methodology/approach – The research was conducted at the Air Tiris sub-district office, Kampar Regency. This study uses simple linear regression with a sample of 31 employees and data collection using questionnaires and documentation. Hypotheses and data calculate use SPSS versi 25. Findings – Based on the results of the study, it was found that work discipline has a positive effect on employee performance at PT Mitra Dana Putra Utama Finance Pekanbaru. This is reflected in the t-value of 5.869 with a significance of 0.000 and t-table of 2.021, which means t-count > t-table. The influence of work discipline on employee performance is 48.2%, while the remaining 51.8% is influenced by other factors.